การจัดกิจกรรมวิชาการตามโครงสรางของศูนยการศึกษานอกระบบ และการศึกษาตามอัธยาศัยอำเภอทามะกา - มรุธาวานิช ชมพู; เจนอักษร นพดล (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2017)
การวิจัยครั้งนี้มีวัตถุประสงคเพื่อทราบ 1) การจัดกิจกรรมวิชาการตามโครงสรางของศูนย กศน.อำเภอทามะกา 2) แนวทางการพัฒนาการจัดกิจกรรมวิชาการตามโครงสรางของศูนย กศน.อำเภอทามะกา ผูใหขอมูล คือ กลุมบุคลากรทางการศึกษา จำนวน 15 คน และผูรับการบริการทางการศึกษา จำนวน 15 คน รวมทั้งสิ้น 30 คน เครื่องมือที่ใชในการวิจัยเปนแบบสอบถามเกี่ยวกับการจัดกิจกรรมวิชาการตามโครงสรางของสถานศึกษา สถิติที่ใช คือ คาความถี่ รอยละ คามัชฌิมเลขคณิต สวนเบี่ยงเบนมาตรฐาน และการวิเคราะหเนื้อหา ผลการวิจัยพบวา 1. การจัดกิจกรรมวิชาการตามโครงสรางของศูนย กศน.อำเภอทามะกา โดยภาพรวมอยูในระดับมาก เรียงตามลำดับคามัชฌิมเลขคณิตจากมากไปนอย ดังนี้ การศึกษาเพื่อพัฒนาสังคมและชุมชน การศึกษาเพื่อพัฒนาทักษะอาชีพ การจัดกระบวนการเรียนรูตามหลักปรัชญาของเศรษฐกิจพอเพียง การศึกษาเพื่อพัฒนาทักษะชีวิต หองสมุดประชาชน สงเสริมการรูหนังสือ และการศึกษานอกระบบระดับการศึกษาขั้นพื้นฐาน 2. แนวทางการพัฒนาการจัดกิจกรรมวิชาการตามโครงสรางของศูนย กศน.อำเภอทามะกา มีแนวทางดังนี้ 1) กำหนดใหเรียนรูตามความสนใจและการใชรายการโทรทัศนเพื่อการศึกษา 2) ใหสงเสริมหองสมุดประชาชนใหเปนหองสมุดมีชีวิต 3) ใหมีการพัฒนาระบบฐานขอมูลผูไมรูหนังสือ 4) นิเทศติดตามหลักสูตรอาชีพ 5) ใหมีการบูรณาการทักษะชีวิตในกลุมสาระการเรียนรูทั้ง 8 สาระ 6) ใหมีการบูรณาการความรู ทักษะสำหรับการศึกษาเพื่อพัฒนาสังคมและชุมชนโดยใชชุมชนเปนฐาน 7)กำหนดใหยึดหลักสำคัญในการพัฒนาคนใหเปนศูนยกลางโดยปลูกฝงหลักปรัชญาของเศรษฐกิจพอเพียง ใหเกิดความตระหนักและฝงรากลึกภายในอยางยั่งยืน MANAGEMENT OF ACADEMIC ACTIVITIES BASED ON THE STRUCTURES OF THAMAKA DISTRICT NON – FORMAL AND INFORMAL EDUCATION CENTER The objectives of this research were to determine 1) the academic activities as preferred by the Thamaka district non-formal and informal education center. 2) the acknowledge ways to improve the deployment of academic activities as preferred by the Thamaka district non-formal and informal education center. The respondents were 30 persons divided into two groups; group of personnel, comprised of executives - government officer, employees and temporary workers totally 15 persons and group of audience, an academic career, agriculture, industry and services totally 15 persons. The instruments used in this research were a questionnaire about the event, academics, according to the structure of the Thamaka district non-formal and informal education center. The statistical used for this research were frequency, percentage, arithmetic mean, standard deviation and content analysis. The results of the research are as followed. 1. The overall satisfactory level for the academic activities that was created by the Thamaka district non-formal and informal education center is high. The ranking of the activities from the most satisfy to the least were as follow education for society and community development, education for occupational skills development, learning process management by sufficient economy philosophy, education for life skills development, public library, literary promotion and non-formal education in basic education level. 2. The development guidelines for the creation of academic activities by the Thamaka district non-formal and informal education center were as followed 1) learner can choose freely base on their personal interest and use television channel for education 2) create lively atmosphere in community library 3) create database of uneducated citizen 4) supervision and monitoring on occupational curriculum 5) integrated life skills within the 8 leaning departments 6) integrate the knowledge and skill about education for improve the society 7) focus on develop the individual by embedded sufficient economy philosophy to create long term awareness and sustainability.